POLA KOMUNIKASI INTERPERSONAL ORANG TUA DAN ANAK DALAM MEMAHAMI BAHAYA GADGET DI TANGERANG - Sri Lestari (Universitas Mercu Buana, 2022)
Technological developments have spread among the community, including children. Currently, not a few children have and are good at operating gadgets. Gadgets can have a positive and negative impact on children. Because it is necessary for parents to provide direction to children so as not to be affected by the negative impact of gadgets by using effective communication patterns. Communication patterns are needed to analyze how the picture of communication that occurs between parents and children as active gadget users. The method used in this research is descriptive qualitative accompanied by in-depth interviews (in-depth interviews) in collecting the data needed for research. The results of this study were obtained through analysis of the recap of the results of indepth interviews with each informant. It is shown that indeed every parent has their own way of educating their children, especially in playing gadgets. Obtained from 5 families (Mother and Child), 1 family that applies permissive communication patterns, 2 families that apply democratic communication patterns and 2 families that apply authoritarian communication patterns.